2010
DOI: 10.2147/ndt.s12605
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric diagnoses in patients with burning mouth syndrome and atypical odontalgia referred from psychiatric to dental facilities

Abstract: BackgroundBurning mouth syndrome (BMS) and atypical odontalgia (AO) are two conditions involving chronic oral pain in the absence of any organic cause. Psychiatrically they can both be considered as “somatoform disorder”. From the dental point of view, however, the two disorders are quite distinct. BMS is a burning or stinging sensation in the mouth in association with a normal mucosa whereas AO is most frequently associated with a continuous pain in the teeth or in a tooth socket after extraction in the absen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
(27 reference statements)
0
39
0
Order By: Relevance
“…In recent study, Nixdorf et al reported the frequency of nonodontogenic pain in patients who had undergone endodontic procedures was approximately 3.4%, that is, nonodontogenic pain is not an uncommon outcome after root canal treatment 19. In other recent study, Takenoshita et al reported that for burning mouth syndrome, the complaints occurred after dental treatment in 38.9%, after other medical treatment in 10.3%, after stressful or emotional events in 10.3%, and spontaneously in 36.5%, that is, more than on third of patients of Burning mouth syndrome relate time of onset to a dental procedures 20. The patient can misunderstand the pain which is actually nonodontogenic pain, occurs because of the dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In recent study, Nixdorf et al reported the frequency of nonodontogenic pain in patients who had undergone endodontic procedures was approximately 3.4%, that is, nonodontogenic pain is not an uncommon outcome after root canal treatment 19. In other recent study, Takenoshita et al reported that for burning mouth syndrome, the complaints occurred after dental treatment in 38.9%, after other medical treatment in 10.3%, after stressful or emotional events in 10.3%, and spontaneously in 36.5%, that is, more than on third of patients of Burning mouth syndrome relate time of onset to a dental procedures 20. The patient can misunderstand the pain which is actually nonodontogenic pain, occurs because of the dental procedures.…”
Section: Discussionmentioning
confidence: 99%
“…10 Although preclinical data in cats 52,53 and rats 54 support functional alterations in trigeminal brainstem neurons following tooth pulp extirpation, evidence from primates, including humans, is lacking. Dental procedures preceding PDAP onset have been anecdotally described, with reported occurrence of 54% 55 up to 83%. 21 By contrast, other studies have reported that 24% 55 to 64% 56 of the patients with pain did not have a preceding dental procedure.…”
Section: Discussionmentioning
confidence: 99%
“…Dental procedures preceding PDAP onset have been anecdotally described, with reported occurrence of 54% 55 up to 83%. 21 By contrast, other studies have reported that 24% 55 to 64% 56 of the patients with pain did not have a preceding dental procedure. The evidence of increased brain activation in areas associated with sensory-discriminative and cognitive aspects of pain processing (eg, thalamus, SI, SII, insula, prefrontal cortex) as well as an integrative cortical area related to somatosensation (IPL) 38,57,58 support the hypothesis of altered central neural mechanisms in PDAP pain.…”
Section: Discussionmentioning
confidence: 99%
“…In the last decade there have been three articles published that assessed psychosocial factors in patients with PDAP, all employing a case-control study design (28,37,38). The first study used the SCL-90 questionnaire to assess this domain for ten cases plus ten matched controls.…”
Section: Proposed Mechanisms Underlying Pdapmentioning
confidence: 99%
“…The third study was restricted to patients being referred from psychiatric facilities and compared patients with PDAP to those with burning mouth syndrome (BMS), but with no pain-free controls (38). Of the 36 patients with PDAP and pre-existing records, the referring clinic had given the following diagnoses: 19 (53%) had a somatoform disorder, 8 (22%) a mood disorder, and 14 (39%) had no psychiatric diagnosis.…”
Section: Proposed Mechanisms Underlying Pdapmentioning
confidence: 99%